1995
DOI: 10.3892/or.2.5.805
|View full text |Cite
|
Sign up to set email alerts
|

Instability at Microsatellite Sequences in Spontaneously Aborted Human Embryos Provides Evidence for a Novel Mechanism for Recurrent Miscarriages

Abstract: Abstract. Several factors have been proposed to confer a risk for abortion of the embryo. However, the aetiology of spontaneous abortions remains unclear. In the present study we investigated if an increased mutational rate occurs in the embryonic tissue and whether this phenomenon is associated with recurrent miscarriage. The mutational rate was assessed in 30 spontaneously aborted embryos using a bank of 8 highly polymorphic microsatellite markers, each one located on a different chromosome. The microsatelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In addition, recent studies suggested that MI is also a detectable phenomenon in spontaneously aborted embryonic tissues (17)(18)(19). MI is the direct result of decreased accuracy in DNA repair and replication and it reflects an elevated mutational rate which indicates destabilization in the genome.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, recent studies suggested that MI is also a detectable phenomenon in spontaneously aborted embryonic tissues (17)(18)(19). MI is the direct result of decreased accuracy in DNA repair and replication and it reflects an elevated mutational rate which indicates destabilization in the genome.…”
Section: Resultsmentioning
confidence: 99%
“…Several factors have been implicated: chromosomal and genomic alterations [1][2][3][4], anatomical defects of the uterus [5][6], endocrinological and immunological disorders [7][8][9], as well as bacteria and virus infections such as rubella and herpes viruses [10,11]. At present there are probably more than 100 different herpes viruses.…”
Section: Introductionmentioning
confidence: 99%
“…In samples that came from a normal birth, only 8% (1 of 12 cases) had MSI. THRA1 and D6S344 presented instability in 5 of the cases whilst D7S531 did not present MSI [152]. Both THRA1 and D6S344 have been found to be highly polymorphic microsatellite markers in other studies [157][158][159][160].…”
Section: Microsatellite Instability In Infertility and Recurrent Misc...mentioning
confidence: 70%
“…In this section we have discussed MSI occurrences in infertile patients independent of genomic instability syndromes. After searching the literature, we found four papers [152][153][154][155], that reported links between MSI and infertility/RM, independent of genomic instability syndromes. We have identified that from these four studies that MSI may be a common feature in idiopathic infertility.…”
Section: Microsatellite Instability In Infertility and Recurrent Misc...mentioning
confidence: 99%